Early Childhood Behavior Patterns in Merpati Hamlet, Naru Village - Prodenty Ene; Maria B. Ndai; Maria A. Ida; Wilhelmina Menge (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
Education is a place to form a good image in humans so that they develop their full potential. SISDIKNAS Law No. 20 of 2003 education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves and society. Formal education is education that can be obtained by participating in activities or educational programs that are structured and planned by government agencies, for example through schools or universities, while non-formal education is education that can be obtained through activities of daily life that are not bound by institutions formed by the government, for example learning through experience, self-study through books and learning through others. The purpose of this writing is to find out the problems of early childhood in Merpati Hamlet, Naru Village and as an assignment for the Early Childhood Cognitive Development course.